2016
DOI: 10.1016/j.scitotenv.2016.04.090
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of enteric adenovirus and poliovirus removal by coagulation processes and suitability of bacteriophages MS2 and φX174 as surrogates for those viruses

Abstract: We evaluated the removal of enteric adenovirus (AdV) type 40 and poliovirus (PV) type 1 by coagulation, using water samples from 13 water sources for drinking water treatment plants in Japan. The behaviors of two widely accepted enteric virus surrogates, bacteriophages MS2 and φX174, were compared with the behaviors of AdV and PV. Coagulation with polyaluminum chloride (PACl, basicity 1.5) removed AdV and PV from virus-spiked source waters: the infectious AdV and PV removal ratios evaluated by means of a plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
4
32
0
1
Order By: Relevance
“…Studies have shown that some coagulants are toxic to viruses, although the virucidal effect varies among different types of viruses. Bacteriophage MS2 was found to be more sensitive to polyaluminum chloride than enteric adenoviruses and poliovirus [19]. Thus, MS2, as a traditional surrogate virus, may not properly represent the fate of enteric viruses during the coagulation/sedimentation process.…”
Section: Removal Through As High Rate Clarification and Dual Mediummentioning
confidence: 99%
“…Studies have shown that some coagulants are toxic to viruses, although the virucidal effect varies among different types of viruses. Bacteriophage MS2 was found to be more sensitive to polyaluminum chloride than enteric adenoviruses and poliovirus [19]. Thus, MS2, as a traditional surrogate virus, may not properly represent the fate of enteric viruses during the coagulation/sedimentation process.…”
Section: Removal Through As High Rate Clarification and Dual Mediummentioning
confidence: 99%
“…AdV type 40 Dugan strain (ATCC VR-931), CV B5 Faulkner strain (ATCC VR-185), HAV IB HM175/18f strain (ATCC VR-1402), and MNV type 1 CW1 strain (ATCC PTA-5935) were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA) and propagated in human lung carcinoma epithelial cells (A549 cells; ATCC CCL-185, obtained from ATCC), buffalo green monkey kidney epithelial cells (BGM cells; kindly supplied by Dr. Daisuke Sano, Hokkaido University, Sapporo, Japan), fetal rhesus monkey kidney epithelial cells (FRhK-4 cells; ATCC CRL-1688, obtained from ATCC), and murine macrophage cells (RAW264.7 cells; ATCC TIB-71, obtained from ATCC), respectively. Details of the propagation and purification of AdV, CV, HAV, and MNV have been described in previous reports (Shirasaki et al, 2016;Shirasaki et al, 2017a).…”
Section: Human Enteric Viruses Mnv Bacteriophages and Pmmovmentioning
confidence: 99%
“…The concentrations of AdV, CV, HAV, and MNV in the purified solutions were approximately 10 5-6 , 10 7 , 10 5-6 , and 10 6 plaque-forming units (PFU)/mL, respectively, based on the results of plaque assays (Shirasaki et al, 2016;Shirasaki et al, 2017a).…”
Section: Human Enteric Viruses Mnv Bacteriophages and Pmmovmentioning
confidence: 99%
See 2 more Smart Citations